Editor’s Introduction: What Does Surveillance Literature Offer Us? - Brown, Stephanie J. (Surveillance & Society, 2026)
This article serves as the editor’s introduction to the Surveillance & Society special issue on “Surveillance and Literature.” It offers a synopsis of important developments in the relationship between literary studies and surveillance studies, with an emphasis on the years since surveillance studies’ late-2000s “cultural turn” (Monahan 2011). These developments include the broadening of the category of surveillance art to include literature and other media that are not primarily visual; the deeply-felt influence of scholars of race in general, and Blackness in particular, on both surveillance and literary studies; and a reckoning with “surveillance capitalism” (Zuboff 2019) as an holistic framework for grasping the forces structuring contemporary surveillance. The article surveys recent work in literary surveillance studies and the essays in the issue, highlighting a shared focus on the affordances of literary work. These affordances include: understanding and responding to historical and contemporary surveillance practices, delineating forms of relationship among the watcher, the watched, and the powers that authorize surveillance, exploring the sensorium made available through narratives of surveillance, narrating resistance under surveillance regimes, and examining the various political projects mobilized by surveillance literature. The introduction maps out the issue’s expansive historical and geographic coverage and indicates how the issue’s authors take up some of surveillance studies’ key concepts. It concludes by gesturing to future directions for literary and surveillance scholars, and to the project of excavating modes of futurity imagined by literary surveillance narratives.